Preparation method of nano tungsten carbide

The preparation process of nano-tungsten carbide is simplified through the one-time carbonization process, and the problems of complex processes and high cost in the solid phase method are solved, and the short process preparation and low-cost production of high-purity nano-tungsten carbide are achieved, which is suitable for large-scale applications.

CN119240702APending Publication Date: 2025-01-03HUNAN BOYUN DONGFANG POWDER METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411675665.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing nano tungsten carbide preparation methods have problems such as complex process flow, high production costs, many impurities introduced, and low efficiency. In particular, the use of ammonium paratungstate decomposition and carbonization method in the solid phase method requires multiple intermediate processes and high-cost tungsten source.

Method used

Using a one-time carbonization process, the tungsten source and carbon black are mixed in a preset ratio and then dried and pressurized, and nano tungsten carbide powder is directly obtained, which simplifies the process and reduces the production cycle and cost. Specific steps include stirring and mixing, drying, sieving and carrying out pressurized reaction in a pressure furnace.

Benefits of technology

It realizes the short process preparation of high-purity nano-tungsten carbide, avoids the introduction of impurities, reduces production costs and cycles, improves the controllability of the reaction process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240702A_ABST
    Figure CN119240702A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano tungsten carbide, which comprises the following steps: S1, mixing a tungsten source and carbon black according to a preset proportion, and then drying and sieving to obtain mixed powder; and S2, the mixed powder obtained in the step S1 is subjected to a pressurized reaction, and the nano tungsten carbide powder is obtained. According to the method disclosed by the invention, the nano tungsten carbide is directly obtained through a one-time carbonization process, so that intermediate procedures in an existing solid phase method are simplified, the production cost is effectively reduced, the production period is effectively shortened, and short-process preparation of the high-purity nano tungsten carbide powder is realized. Compared with traditional methods such as a liquid phase method and a gas phase method, the method is low in raw material cost, simple in technological process, good in reaction process controllability and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a method for preparing nano tungsten carbide. Background Art

[0002] Nano cemented carbide (WC grain size less than 0.2μm) has higher hardness and strength than traditional cemented carbide, which can effectively solve the problem of ultra-high-speed cutting of difficult-to-process materials such as composite materials and hardened steel, greatly improve the machining efficiency, and is the development direction of cemented carbide. The key to preparing nano cemented carbide is mainly two aspects: one is nano tungsten carbide raw material powder; the other is to inhibit grain growth during sintering. Therefore, in order to prepare nano cemented carbide with good mechanical properties, obtaining nano WC powder is the basis.

[0003] There are many methods for preparing nano-tungsten carbide reported in the literature. According to the medium form in the reaction system, they are divided into gas phase method, liquid phase method and solid phase method.

[0004] The gas phase method usually uses a gaseous or gasifiable tungsten source to react with a gaseous carbon source to prepare nano-tungsten carbide. In the gas phase method, the contact area of ​​each medium is large, and even contact is made at the molecular level, and its diffusion resistance can be significantly reduced. In addition, there are large nucleation sites between the gas media, which is conducive to obtaining nano-WC powder. However, the cost of the gaseous tungsten source is high, and in the actual preparation process, the controllability of the reaction process is poor.

[0005] The liquid phase method mainly includes the sol-gel method and the hydrothermal method. The sol-gel method is to dissolve the tungsten compound and the carbon source in a solvent to form a uniform sol, and then convert the solution into a gel through the gelation process of the sol. Finally, after drying, calcination and other treatments, nano-tungsten carbide is obtained; the hydrothermal method is to dissolve the tungsten compound and the carbon source in water, and then put the solution into a high-pressure reactor to react under high temperature and high pressure conditions. The liquid phase method requires the use of solvents and has high process control requirements.

[0006] The solid phase method directly mixes the solid tungsten source and the solid carbon source under mechanical force and directly forms ultrafine tungsten carbide powder through carburizing reaction, or further synthesizes nano tungsten carbide powder at high temperature under protective atmosphere. At present, the ammonium paratungstate decomposition carbonization method in the solid phase method is mainly used in large-scale production: APT→tungsten oxide→tungsten (W) powder→WC powder. APT is calcined as raw material to produce tungsten oxide, and then a reduction furnace is used to reduce tungsten oxide to W powder, and then carbon black is added. After being evenly mixed, it is carbonized in a carbonization furnace to prepare nano WC powder. There are disadvantages such as complex process flow, high production cost, introduction of many impurities, and low efficiency. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing nano-tungsten carbide, which directly obtains nano-tungsten carbide through a one-time carburization process, simplifies the intermediate steps in the prior art, effectively reduces the production cost and production cycle, and realizes the short-process preparation of high-purity nano-tungsten carbide powder.

[0008] The present invention provides a method for preparing nano tungsten carbide, comprising the following steps:

[0009] S1. Mixing the tungsten source and carbon black in a preset ratio, and then drying and sieving to obtain a mixed powder;

[0010] S2. The mixed powder obtained in step S1 is subjected to pressure reaction to obtain nano-tungsten carbide powder.

[0011] Furthermore, in step S1, the tungsten source is any one of ammonium metatungstate and ammonium paratungstate.

[0012] Furthermore, the preset ratio of tungsten source to carbon black is specifically: the molar ratio of tungsten source: carbon source is 1:(3-4).

[0013] Furthermore, the tungsten source and carbon black are commercially available products.

[0014] Further, the tungsten source and the carbon black are mixed using a mixer, with alcohol being used as a stirring medium.

[0015] Specifically, the process parameters of the mixer mixing are: the mixer speed is 100-200 r / min, and the mixing time is 4-8 h.

[0016] Furthermore, the drying process conditions are: drying at 60-100° C. for 2-6 hours.

[0017] Furthermore, the dried product needs to be sieved through a 100-mesh sieve, and the product under the sieve is taken as the mixed powder finally obtained in step S1.

[0018] Furthermore, step S2 specifically includes: placing the mixed powder in a pressure furnace, and performing a pressure reaction under a reducing atmosphere or a neutral atmosphere to obtain nano tungsten carbide powder.

[0019] Furthermore, the reducing atmosphere is hydrogen, and the flow rate during ventilation is 200 to 2000 L / h.

[0020] Furthermore, the neutral atmosphere is argon, and the flow rate during ventilation is 200 to 2000 L / h.

[0021] Furthermore, the process conditions of the pressure reaction are: the temperature of the pressure reaction is 1100-1200° C., the time is 30-150 min, and the pressure is 1-8 MPa.

[0022] Beneficial effects of the present invention:

[0023] (1) Compared with the traditional solid phase method of using APT as a raw material to first calcine to produce tungsten oxide, and then reduce and carburize to prepare tungsten carbide, the method of the present invention has a short process flow, can effectively avoid the introduction of impurities, reduce production costs and production cycles, and improve the purity of tungsten carbide products;

[0024] (2) Compared with traditional liquid phase method, gas phase method and other methods, the method of the present invention has low raw material cost, simple process, good controllability of the reaction process, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The electron microscope morphology of the nano-tungsten carbide obtained in Example 1;

[0026] Figure 2 The nano-tungsten carbide phase detection result obtained in Example 1;

[0027] Figure 3 The electron microscope morphology of the nano-tungsten carbide obtained in Example 2;

[0028] Figure 4 The nano-tungsten carbide phase detection result obtained in Example 2;

[0029] Figure 5 The electron microscope morphology of the nano-tungsten carbide obtained in Example 3;

[0030] Figure 6 The nano-tungsten carbide phase detection result obtained in Example 3;

[0031] Figure 7 The electron microscope morphology of the nano-tungsten carbide obtained in Comparative Example 1;

[0032] Figure 8 The nano-tungsten carbide phase detection result obtained in Comparative Example 1;

[0033] Fig. 9 The electron microscope morphology of the nano-tungsten carbide obtained in Comparative Example 2;

[0034] Fig.10 The nano-tungsten carbide phase detection result obtained in Comparative Example 3;

[0035] Fig.11 This is the electron microscope morphology of the nano-tungsten carbide obtained in Comparative Example 3. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0038] Example 1

[0039] According to the molar ratio of tungsten source: carbon source of 1:4, 297.4g of ammonium metatungstate and 4.8g of carbon black were weighed and put into a blender, and then 500ml of alcohol was added. The mixture was stirred at 100r / min for 8h. The obtained slurry was dried in an oven at 60°C to constant weight and then passed through a 100-mesh sieve to obtain a mixed powder.

[0040] The obtained mixed powder was placed in a pressure furnace, nitrogen was introduced at a flow rate of 500 L / h, and the mixture was reacted at a temperature of 1150° C. and a pressure of 2 MPa for 90 minutes to obtain nano-tungsten carbide powder.

[0041] The obtained nano-tungsten carbide powder was subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows: Figure 1 The obtained nano-tungsten carbide powder was then tested using an X-ray diffractometer. The results are as follows: Figure 2 shown.

[0042] After testing, the BET of the obtained nano tungsten carbide powder is 3.86m 2 / g, total carbon is 6.16%, free carbon is 0.08%, and oxygen content is 0.41%.

[0043] Example 2

[0044] According to the molar ratio of tungsten source: carbon source of 1:3.5, 297.4g of ammonium metatungstate and 4.2g of carbon black were weighed and put into a blender, and then 500ml of alcohol was added. The mixture was stirred at 200r / min for 10h. The obtained slurry was dried in an oven at 80°C to constant weight and then passed through a 100-mesh sieve to obtain a mixed powder.

[0045] The obtained mixed powder was placed in a pressure furnace, nitrogen was introduced at a flow rate of 1000 L / h, and the mixture was reacted for 110 minutes at a temperature of 1200° C. and a pressure of 5 MPa to obtain nano-tungsten carbide powder.

[0046] The obtained nano-tungsten carbide powder was subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows: Figure 3 The obtained nano-tungsten carbide powder was then tested using an X-ray diffractometer. The results are as follows: Figure 4 shown.

[0047] After testing, the BET of the obtained nano tungsten carbide powder is 3.79m 2 / g, total carbon is 6.21%, free carbon is 0.09%, and oxygen content is 0.34%.

[0048] Example 3

[0049] According to the molar ratio of tungsten source: carbon source of 1:3.6, 313.3g of ammonium metatungstate and 4.3g of carbon black were weighed and put into a blender, and then 500ml of alcohol was added. The mixture was stirred at 150r / min for 6h. The obtained slurry was dried in an oven at 100°C to constant weight and then passed through a 100-mesh sieve to obtain a mixed powder.

[0050] The obtained mixed powder was placed in a pressure furnace, nitrogen was introduced at a flow rate of 1500 L / h, and the mixture was reacted for 150 minutes at a temperature of 1100° C. and a pressure of 8 MPa to obtain nano-tungsten carbide powder.

[0051] The obtained nano-tungsten carbide powder was subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows: Figure 5 The obtained nano-tungsten carbide powder was then tested using an X-ray diffractometer. The results are as follows: Figure 6 shown.

[0052] After testing, the BET of the obtained nano tungsten carbide powder is 3.72m 2 / g, total carbon is 6.23%, free carbon is 0.1%, and oxygen content is 0.31%.

[0053] Comparative Example 1

[0054] Ammonium metatungstate was placed in an alumina crucible and calcined in a muffle furnace at a temperature of 700°C for 4 hours to obtain tungsten oxide agglomerates.

[0055] The obtained tungsten oxide agglomerates were crushed by air jet milling equipment. The crushing time was 30 minutes and the air flow rate was 150m 3 / h, gas pressure is 0.06MPa,

[0056] The crushed tungsten oxide (particle size of 0.5 μm) and high-purity carbon black were mixed in a vertical plowshare at a mass ratio of 1:0.19, and the obtained mixture was spray granulated using spray granulation technology and room temperature second drying technology to obtain spherical materials;

[0057] A rotary reduction furnace with six temperature zones is used to reduce and carbonize the obtained spherical material under the protection of nitrogen atmosphere. The temperatures of the six temperature zones from the furnace head to the furnace tail are 850°C, 880°C, 910°C, 950°C, 980°C and 980°C respectively. The rotation speed of the material is 3r / min, and the insulation time from feeding to discharging is 60min, so as to obtain a pre-carbonized material with a chemical composition of WC+W2C.

[0058] The pre-carbonized material was passivated in a molybdenum wire furnace in a carbon monoxide atmosphere at a passivation temperature of 1400°C and a holding time of 30 minutes. After passivation, nano-tungsten carbide with complete and uniform grains was obtained. The specific surface area of ​​the nano-tungsten carbide powder was 3.71 m 2 / g.

[0059] The obtained nano-tungsten carbide powder was subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows: Figure 7 The obtained nano-tungsten carbide powder was then tested using an X-ray diffractometer, and the results were as follows: Figure 8 shown.

[0060] Comparative Example 2

[0061] Ammonium metatungstate APT was calcined at 800℃ for 10min to form purple tungsten; purple tungsten was oxidized in an internal oxidation furnace at 500℃ for 30min to form yellow tungsten; yellow tungsten was ball-milled in a drum mixer for 3h to obtain nano yellow tungsten, and the ball milling speed was 45r / min; nano yellow tungsten was mixed with carbon and pressed to obtain a pressed green body, which was reduced in a N2 environment at 1000℃ to obtain a W and C mixed green body, and then carbonized in a N2 environment at 1350℃ to form a WC block; the WC block was crushed to obtain a specific surface area of ​​3.15m 2 / g of nano WC powder.

[0062] The obtained nano-tungsten carbide powder was subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows: Fig. 9 shown.

[0063] Comparative Example 3

[0064] Dissolve 100 kg of water-soluble ammonium metatungstate, 54 kg of glucose, 0.6 kg of ammonium metavanadate and 0.9 kg of ammonium dichromate in pure water whose mass is 1.0 times of the total mass of the solids, stir evenly at 80°C to obtain a mixed slurry with a pH of 4;

[0065] The obtained mixed slurry was subjected to centrifugal spray drying to obtain a spherical precursor composite powder, wherein the conditions of the centrifugal spray drying were: an inlet air temperature of 260°C, an outlet air temperature of 140°C, an atomizer speed of 15000 r / min, and a feed rate of 3.4 kg / min;

[0066] The obtained spherical precursor composite powder was calcined at 600°C for 60 min under nitrogen, and then the spherical shell was broken by dry ball milling to obtain carbon-coated nano-WO3 powder.

[0067] The obtained carbon-coated nano-WO3 powder was reduced and carbonized at 1200°C in an atmosphere of H2:CH4 (volume ratio) = 98.5:1.5 for 60 min to obtain a specific surface area of ​​5.35 m 2 / g of nano WC powder.

[0068] The obtained nano-tungsten carbide powder was tested by X-ray diffractometer. Fig.10 The obtained nano-tungsten carbide powder was then subjected to electron microscope experiment to observe its microscopic morphology. The results are as follows Fig.11 shown.

Claims

1. A method for preparing nano tungsten carbide, characterized in that: The following steps are involved: S1. Mixing the tungsten source and carbon black in a preset ratio, and then drying and sieving to obtain a mixed powder; S2. The mixed powder obtained in step S1 is subjected to pressure reaction to obtain nano-tungsten carbide powder.

2. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: In step S1, the tungsten source is any one of ammonium metatungstate and ammonium paratungstate; the tungsten source and carbon black are commercially available products.

3. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: The preset ratio of tungsten source to carbon black is specifically: the molar ratio of tungsten source: carbon source is 1:(3-4).

4. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: The tungsten source and the carbon black are mixed by a stirrer, with alcohol being used as a stirring medium; the process parameters of the stirring machine are as follows: the stirring machine speed is 100-200 r / min, and the stirring time is 4-8 h.

5. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: The drying process conditions are: drying at 60-100°C for 2-6 hours.

6. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: The product obtained after drying needs to be sieved through a 100-mesh sieve, and the product under the sieve is taken as the mixed powder finally obtained in step S1.

7. The method for preparing nano-tungsten carbide according to claim 1, characterized in that: Step S2 specifically includes placing the mixed powder in a pressure furnace and performing a pressure reaction under a reducing atmosphere or a neutral atmosphere to obtain nano tungsten carbide powder.

8. The method for preparing nano-tungsten carbide according to claim 7, characterized in that: The reducing atmosphere is hydrogen, and the flow rate during ventilation is 200-2000 L / h.

9. The method for preparing nano-tungsten carbide according to claim 7, characterized in that: The neutral atmosphere is argon gas, and the flow rate during ventilation is 200 to 2000 L / h.

10. The method for preparing nano-tungsten carbide according to claim 7, characterized in that: The process conditions of the pressure reaction are as follows: the temperature of the pressure reaction is 1100-1200° C., the time is 30-150 min, and the pressure is 1-8 MPa.